A Protocol Review for IPTV and WebTV Multimedia Delivery Systems - Lourdes Beloqui Yuste; Hugh Melvin (Communications - Scientific letters of the University of Zilina, 2012)
This paper reviews the key protocols used for multimedia delivery both over privately owned managed IP Networks such as IPTV and public non-managed IP Networks such as WebTV. Within these two worlds, the choice between protocols is based on the characteristics of the multimedia service required, the media server and the client’s receiver.Users have different expectations of these two delivery platforms and also of different output devices such as TV, PC, tablet or mobile phone. In an IPTV environment, which is a paid-service, users demand the Quality of Service (QoS) they pay for; different quotas provide different services to users. On the other hand, with WebTV, which is a free service, clients have lower quality expectations.There are multiple multimedia delivery systems used across both platforms, using different protocols to deliver multimedia from server to one or multiple clients. These include Real-Time Protocol (RTP), Real-Time Control Protocol (RTCP), Real-Time Streaming Protocol (RTSP), Real-Time Messaging Protocol (RTMP), Hypertext Transfer Protocol (HTTP), HTTP Live Streaming (HLS) and Microsoft Smooth Streaming Protocol (MS- SSTR).RTP, RTCP and RTSP are the main protocols used in IPTV while RTMP, HTTP, HLS and MS-SSTR are protocols used mainly for WebTV. This paper will explore the main differences and similarities between them and the reasons behind the choice of one or the other. This review paper also briefly outlines a testbed being developed by the authors to synchronise media streams using a subset of these protocols.